Analisis Terhadap Kompatibilitas Al-Qur’an Dan Demokrasi Indonesia (Tinjauan Etis Perspektif Tafsir Tematik) - Lutfiyatiun Naqiyah (Prodi Ilmu Al Qur'an dan Tafsir, 2026)
Abstract This article examines the compatibility between Indonesia’s democratic system and the normative values of the Qur’an through a thematic Qur’anic interpretation combined with political ethics analysis. Responding to the limitations of apologetic and dichotomous approaches in existing Islam–democracy debates, this study positions the Qur’an not as a source of legitimation for specific political systems, but as a framework of public ethics for critically evaluating political power. Employing a qualitative library-based method, the research analyzes Qur’anic verses on shūrā (consultation), justice (‘adl), trust (amānah), and obedience to authority (ulū al-amr), alongside classical and contemporary exegetical interpretations. The findings demonstrate that Indonesia’s democracy is normatively compatible with Qur’anic values at the level of ethical objectives, despite procedural and historical differences. Such compatibility depends on the internalization of justice, consultation, and accountability within political culture and governance practices. This article contributes to contemporary Qur’anic studies by advancing a critical and contextual application of thematic interpretation, positioning the Qur’an as a source of moral critique rather than passive legitimation of democratic power in the Indonesian socio-political context. Keywords: Qur’an; Indonesian democracy; political ethics; thematic interpretation; shūrā.